Quantitative forensic evaluation of bite marks with the aid of a shape analysis computer program: Part 2; 'SCIP' and bite marks in skin and foodstuffs - Nambiar, P.; Bridges, T.E.; Brown, K.A. (1995)
In a previous paper, we have shown that the use of an interactive shape analysis computer program ('SCIP') and the derivation of a quantitative Similarity Index greatly facilitated the comparison of experimental flat wax bite marks with the dentition of various 'suspects' and the identification of the agent producing the bite. In this study, 'SCIP' was employed in an attempt to quantify the comparison, in the form of the Similarity Index (S.I.), between the 'offender's' teeth and the bite marks produced on foodstuffs and on human skin, under experimental conditions. The use of 'SCIP' and the S.I. is recommended as a routine means of eliminating suspects in bite mark cases. If a reasonable number of reference points have been registered in the bitten material and particularly if the perpetrator has any unusual features in the anterior dentition, the matching of the bite mark with the actual offender is a possibility with this method.